Electrochemical sensing of glucose by chitosan modified graphene oxide. (14th January 2020) - Poletti, Fabrizio; Favaretto, Laura; Kovtun, Alessandro; Treossi, Emanuele; Corticelli, Franco; Gazzano, Massimo; Palermo, Vincenzo; Zanardi, Chiara; Melucci, Manuela
Abstract: Graphene oxide (GO) coated electrodes provide an excellent platform for enzymatic glucose sensing, induced by the presence of glucose oxidase and an electrochemical transduction. Here, we show that the sensitivity of GO layers for glucose detection redoubles upon blending GO with chitosan (GO+Ch) and increases up to eight times if covalent binding of chitosan to GO (GO−Ch) is exploited. In addition, the conductivity of the composite material GO−Ch is suitable for electrochemical applications without the need of GO reduction, which is generally required for GO based coatings. Covalent modification of GO is achieved by a standard carboxylic activation/amidation approach by exploiting the abundant amino pendants of chitosan. Successful functionalization is proved by comparison with an ad-hoc synthesized control sample realized by using non-activated GO as precursor. The composite GO−Ch was deposited on standard screen-printed electrodes by a drop-casting approach. Comparison with a chitosan-GO blend and with pristine GO demonstrated the superior reliability and efficiency of the electrochemical response for glucose as a consequence of the high number of enzyme binding sites and of the partial reduction of GO during the carboxylic activation synthetic step.